The spirituality of entheogenic drugs of the pre-Columbian world studied by Quirce-Balma: an approach from Intercultural Theology - Vargas Carranza, Alejandro (2018)
The spirituality of the entheogenic drugs of the pre-Columbian world has been neglected in Latin American theology, even condemned from the most traditional theological lines. In this sense, the contributions of the pre-Columbian entheogenic spirituality studied by Quirce-Balma for the theological reflection in Latin America from an intercultural perspective are determined, for it is given a dialogical approach between the ethnopsychofarmacology of QuirceBalma, the intercultural theology, the theology of Liberation and traditional theology. It also recognizes the spirituality of the entheogenic drugs of the preColumbian world as cultural memory, which enriches intercultural theology and constitutes a means for the dignification of the world.